Understanding resource partitioning in three species of Gobiidae living in the warm-temperate Sundays Estuary - Ndaleni, Phumza Malibongwe (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Estuaries represent a transition zone where saline water combines with freshwater, and this results in temporal and spatial variability in both biotic and abiotic parameters. Because the environmental gradient changes so rapidly in areas and the estuarine environment is harsh, fish need to either be able to specialise to one particular suite of abiotic contexts or have the physiological mechanisms to allow them to move throughout the gradient of the estuary. Apart from this, other factors such as climate change, habitat degradation, over exploitation of resources and the introduction of alien species also negatively influence fish species living in estuaries. These anthropogenic stressors can cause species exclusion in areas which were previously suitable for species with particular suites of traits. Measuring resource partitioning within functional groups not only helps in determining the functional structure of communities but also explains how organisms use resources in a community. Resource partitioning studies provide a useful conceptual framework to understand species interactions in a community and identify major resource dimensions along which species segregate. This study aimed to describe resource partitioning among the Gobiidae species, as the family is well represented in South African estuaries (24 species), is highly abundant and has several species which co-exist in individual estuaries. To accomplish this, different forms of resource partitioning that promote the coexistence of the three most abundant species found in warm-temperate South African estuaries; the Knysna sand goby Psammogobius knysnaensis (Smith, 1935), Prison goby Caffrogobius gilchristi (Boulenger, 1898) and River goby Glossogobius callidus (Smith, 1937) were investigated in the Sundays Estuary. This was accomplished by determining the reproductive biology, interspecific differences in feeding morphology, feeding ecology and habitat partitioning among the three species. The distribution and abundance of potential prey in the estuary (mesozooplankton and macrozoobenthic communities) were investigated, with both mesozooplankton and macrozoobenthic communities grouping into three distinct communities along the environmental gradient. Feeding morphological traits responsible for prey location, chasing, capture, mastication, ingestion and digestion were investigated. Little morphological overlap was observed between P. knysnaensis and C. gilchristi, indicating little dietary overlap between these two species. In contrast, the feeding morphology of Glossogobius callidus overlapped with both P. knysnaensis and C. gilchristi, indicating the potential to compete with both species for food. The trophic ecology of the three species was investigated using stomach content analysis, whereby prey abundance, frequency of occurrence and percentage of volume were determined. For P. knysnaensis, the incorporation of cyclopoids and ostracods decreased with fish size and that of bivalves and amphipods increased. Caffrogobius gilchristi was found to be a specialist feeder on cyclopoids but as the species increased in size the incorporation of amphipods, mysids, brachyurans and gastropods increased. Glossogobius callidus was found to be a generalist feeder, feeding on cyclopoids, amphipods and chironomids. The incorporation of cyclopoids decreased with fish size and the consumption of large sized amphipods and chironomids increased with fish size. To assess their reproductive biology, gonadosomatic index (GSI) was used to study the breeding season. In all three species, reproduction peaked in spring and summer, and this is associated with peak phytoplankton and zooplankton biomass in estuaries. Length at 50% maturity and fecundity were also determined. The three species predominated in different locations in the estuary, which explains why they were able to use similar resources and reproduce at the same time. Psammogobius knysnaensis was abundant in the sandy mouth region, with sediment type and prey (bivalves and mysids) availability affecting its distribution. Caffrogobius gilchristi was abundant in the muddy lower reaches of the estuary, with its distribution influenced by sediment composition and temperature. Glossogobius callidus was abundant in the turbid upper reaches, with its distribution influenced by prey (amphipods) availability and turbidity. Different habitat preferences and diet among the specific size ranges enabled coexistence among the species. This explains the high abundances and coexistence of gobies in South African estuaries.
Keywords: Gobiidae -- South Africa Sundays Estuary (Eastern Cape); Gobiidae Reproduction; Gobiidae Food; Gobiidae Geographical distribution; Gobiidae Morphology; Resource partitioning (Ecology)